EVALUATION OF PRESCRIBING INDICATORS FOR PEADIATRIC OUTPATIENTS UNDER SIX YEARS OLD IN DISTRICT HOSPITALS OF CAN THO CITY IN THE PERIOD OF 2015-2016 - Nguyen, Hung Phuc; MY, HUONG VO THI; CHI, THANH PHAN (International Journal of Pharmacy and Pharmaceutical Sciences, 2019)
Objective: Examining and comparing the primary and supplementary prescribing indicators in pediatric outpatients under six years old. Methods: We performed a comparative cross-sectional study, over nine months, from September 2015. 800 prescriptions for peadiatric patients under 6 y old were collected at 8 district hospitals in Can Tho city to evaluate the primary and supplementary prescribing indicators. The sample was collected prospectively by the systematic selection, with the interval between the patients is 5. The data was analysed and compared to the standard drug use indicators in developing countries recommended by WHO. Results: Average number of drugs per encounter: 4.1, percentage of drugs prescribed by generic name: 94.2%, percentage of encounters with an antibiotic prescribed: 85.8%, percentage of drugs prescribed from essential drugs list by Ministry of Health: 78.7%, percentage of encounters with a corticoid prescribed: 41.7%, percentage of encounters with a vitamin prescribed: 13.1%, average drug cost per encounter: 37.5 thousands VND, percentage of drug costs spent on antibiotics: 55.2%, percentage of drug costs spent on essential drugs: 75.7%, percentage of drug costs spent on corticoid: 1.9%, percentage of drug costs spent on vitamin: 1.4%. Conclusion: The results of this research have identified some issues in outpatient prescribing, which may lead to intervention studies for evaluating changes in these issues in the outpatient clinic.